2017
DOI: 10.1080/13510002.2017.1329917
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene protects against UVB-induced photo-damage through a phosphatidylinositol-3-kinase-dependent Nrf2/ARE pathway in human keratinocytes

Abstract: The present study indicated that Pter effectively protected against UVB-induced photodamage by increasing endogenous defense mechanisms, scavenging UVB-induced ROS, and aiding in damaged DNA repair through a PI3K-dependent activation of Nrf2/ARE pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…While UV irradiation can increase the production of reactive oxygen species and oxidative products [179,180], resveratrol can attenuate UV-induced oxidative stress via upregulation and/or activation of Nrf2. For example, treatment of keratinocytes with resveratrol either before or after UVA irradiation induced >50% increase in Nrf2 content, while increasing content of Nrf2 in the nuclear fraction [86,90]. Similarly, treatment of either normal mice or oxidative-stressed keratinocytes with resveratrol increases Nrf2 expression and activation [98,99], leading to increased expression of phase 2 antioxidant enzymes and reductions in reactive oxygen species [85,90,100], ultimately protecting/ alleviating cell damage induced by UV irradiation or other oxidative stressors.…”
Section: Protection From Uv Irradiation and Antioxidant Defensementioning
confidence: 99%
See 1 more Smart Citation
“…While UV irradiation can increase the production of reactive oxygen species and oxidative products [179,180], resveratrol can attenuate UV-induced oxidative stress via upregulation and/or activation of Nrf2. For example, treatment of keratinocytes with resveratrol either before or after UVA irradiation induced >50% increase in Nrf2 content, while increasing content of Nrf2 in the nuclear fraction [86,90]. Similarly, treatment of either normal mice or oxidative-stressed keratinocytes with resveratrol increases Nrf2 expression and activation [98,99], leading to increased expression of phase 2 antioxidant enzymes and reductions in reactive oxygen species [85,90,100], ultimately protecting/ alleviating cell damage induced by UV irradiation or other oxidative stressors.…”
Section: Protection From Uv Irradiation and Antioxidant Defensementioning
confidence: 99%
“…erefore, resveratrol can sequentially or separately upregulate SIRT1 and Nrf2, while downregulation of Keap1 expression, resulting in increased expression of phase 2 antioxidant enzymes, which in turn protect the skin from UV irradiation-and oxidative stress-induced damage. Finally, one study showed that inhibition of phosphatidylinositol-3-kinase prevented the activation of Nrf2 induced by pterostilbene, a resveratrol analog, suggesting that resveratrol can also activate Nrf2 via activation of phosphatidylinositol-3-kinase [90].…”
Section: Protection From Uv Irradiation and Antioxidant Defensementioning
confidence: 99%
“…Current data also indicate that pterostilobene have protective effect against aged‐related disease. In human keratinocytes, pterostilbene protects against UVB‐induced photo‐damage through phosphatidylinositol‐3‐kinase (PI3K)‐dependent activation of Nrf2/antioxidant response element (ARE) pathway . Pterostilbene suppress the IL‐1β‐induced inflammation and ROS production in chondrocytes by inducing the nuclear translocation of Nrf2 in order to prevent cartilage degeneration .…”
Section: The Effect Of Resveratrol and Pterostilbene On Age‐related Mmentioning
confidence: 99%
“…Importantly, this only works if the tumor model is under pituitary hormone control and was effective in significantly reducing tumor burden against three different melanoma xenograph mouse models (Benlloch et al, 2016). Other reports have shown pterostilbene to activate the Nrf2 pathway (Chiou et al, 2011;Saw et al, 2014;Li et al, 2017). This apparent paradox may be Brought to you by | University of California -Irvine Authenticated Download Date | 5/4/19 12:43 AM explained by the concentration of pterostilbene shown to be effective against melanoma; a low, physiologically relevant dose of pterostilbene was shown to be effective (Benlloch et al, 2016).…”
Section: Antioxidants and Prooxidants: Good Or Harmful?mentioning
confidence: 99%